2021
DOI: 10.1021/acsaem.1c00930
|View full text |Cite
|
Sign up to set email alerts
|

Cation Engineering for Effective Defect Passivation to Improve Efficiency and Stability of FA0.5MA0.5PbI3Perovskite Solar Cells

Abstract: Large organic cations have been widely employed to passivate defects in perovskite solar cells (PSCs). In this research, we study how double ions influence PSC developments. Four additives, namely, BAI, BACl, PEAI, and PEACl, were introduced into the precursor solution during the hybrid PSC preparation, and it is found that they not only improve the crystallization of the perovskite films but also passivate the surface and grain boundary defects, leading to improved PSC performance. BACl is found to be the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…As a result, BA and PA could only occupy the surface or grain boundary position in crystallized films. [31,36,37] As for EA, one would expect lattice insertion by FA substitution due to similar ionic size (Table S1, Supporting Information), if present in final films after thermal annealing, but the absence of lattice variation detectable via XRD test indicated that most EACl was removed during the annealing at 140 °C via evaporation, consistent with the previous report on EACl-engineered MAPbI 3 films. [38,39] Based on the morphological and XRD results presented above, we proposed the crystal growth mechanism for large and favorably oriented grains in films with additives (Figure 3e,f ).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…As a result, BA and PA could only occupy the surface or grain boundary position in crystallized films. [31,36,37] As for EA, one would expect lattice insertion by FA substitution due to similar ionic size (Table S1, Supporting Information), if present in final films after thermal annealing, but the absence of lattice variation detectable via XRD test indicated that most EACl was removed during the annealing at 140 °C via evaporation, consistent with the previous report on EACl-engineered MAPbI 3 films. [38,39] Based on the morphological and XRD results presented above, we proposed the crystal growth mechanism for large and favorably oriented grains in films with additives (Figure 3e,f ).…”
Section: Resultssupporting
confidence: 86%
“…This study revealed that both cation and anion from additives positively influence the performance, with organic cations, i.e., FA and MA, enabling higher performance than inorganic cations Cs + and Rb + , [ 29 ] due to their strong ability to effectively passivate bulk and grain boundary defects. [ 30–32 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of the perovskite film plays a key role in preparing the PSCs with high PCE. ,, As yet, a lot of methods have been proposed to ameliorate the quality of the perovskite thin film, for example, additive engineering, ,, buried engineering, , precursor solvent, and component engineering. , Besides, the antisolvent engineering , has been considered one of the most effective ways to enhance the quality of the perovskite film. In addition to finding more suitable and greener antisolvents or mixing antisolvents engineers, , introducing additives into antisolvents is also an important content of antisolvent engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the perovskite film plays a key role in preparing the PSCs with high PCE. 7,10,11 As yet, a lot of methods have been proposed to ameliorate the quality of the perovskite thin film, for example, additive engineering, 5,12,13 buried engineering, 14,15 precursor solvent, and component engineering. 16,17 Besides, the antisolvent engineering 18,19 has been considered one of the most effective ways to enhance the quality of the perovskite film.…”
Section: ■ Introductionmentioning
confidence: 99%